DNA integrity and viability of testicular cells from diverse wild species after slow freezing or vitrification - Peris-Frau, Patricia; Benito-Blanco, Julia; Martínez-Nevado, Eva; Toledano-Díaz, Adolfo; Castaño, Cristina; Velázquez, Rosario; Pequeño, Belén; Martinez-Madrid, Belén; Esteso, Milagros C.; Santiago-Moreno, Julián (Frontiers in Veterinary Science, 2023)
Cryopreservation of testicular tissues offers new possibilities to protect endangered species, genetically valuable individuals or even the fertility potential of prepubertal individuals who have died unexpectedly. However, the use of this technique still remains a challenge. In this study, slow freezing and vitrification of testicular tissue was investigated to find out which cryopreservation method could better preserve the viability and DNA integrity of testicular germ cells in diverse wild species. Testes were obtained post-mortem from 18 artiodactyls (wild boar, roe deer, dwarf goat, mhor gazelle, European mouflon, African forest buffalo, Malayan tapir, dorcas gazelle, Iberian ibex, gnu, red river hog), 5 primates (colobus monkey, capuchin monkey, mandrill), 8 carnivores (grey wolf, Persian leopard, binturong, European mink, American black bear, suricata) and 2 rodents (Patagonian mara). The testicles belonged to adult individuals and were cut into small pieces and cryopreserved by needle immersed vitrification or uncontrolled slow freezing using a passive cooling device. After warming or thawing, testicular tissues were enzymatically digested and two germ cell types were differentiated based on their morphology: rounded cells (spermatogonia, spermatocytes and early spermatids) and elongated cells (elongated spermatids and spermatozoa). Cell viability was assessed by SYBR-14/propidium iodide while DNA fragmentation by TUNEL assay with fluorescence microscope. Our preliminary results revealed that our uncontrolled slow freezing method better preserved the viability and DNA integrity of elongated cells than vitrification. Such trend was observed in all species, being significant in artiodactyls, carnivores and primates. Similarly, the viability and DNA integrity of rounded cells was also better maintained in primates by uncontrolled slow freezing, while in carnivores, vitrification by needle immersion showed better results in this type of cells. In artiodactyls and rodents both techniques preserved the viability of rounded cells in a similar manner, although the DNA integrity of these cells was greater after needle immersed vitrification in artiodactyls. In conclusion, the effectiveness of each cryopreservation method is affected by the phylogenetic diversity between species and cell type.